Lincoln's Gettysburg Address : a primary source investigation - Olson, Steven P. (New York : Rosen Central, 2005)
This book discusses Lincoln's speech to honor the dead from the Battle of Gettysburg.
Includes index.
Includes chronology.
Includes glossary.
Includes bibliographies.
4-8
Keywords: Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865.; Gettysburg (Pa.), Battle of, 1863.